(untitled) (UNWE Yearbook, 2017)
Focusing on the topic of the specific features of economic texts, the article presents a descriptive textlinguistic model which can be applied to their analysis. On the basis of their textlinguistic features, the author offers a number of tasks so as the selected texts can be employed in a consistent practice aimed at the development of reading and summarizing skills of students at the CEFR levels when teaching German for Specific Purposes.